Xylitol gummy bear snacks: a school-based randomized clinical trial - Roberts Marilyn C; Rothen Marilynn; Milgrom Peter; Riedy Christine A; Ly Kiet A; Zhou Lingmei (BMC, 2008)
Abstract Background Habitual consumption of xylitol reduces mutans streptococci (MS) levels but the effect on Lactobacillus spp. is less clear. Reduction is dependent on daily dose and frequency of consumption. For xylitol to be successfully used in prevention programs to reduce MS and prevent caries, effective xylitol delivery methods must be identified. This study examines the response of MS, specifically S. mutans/sobrinus and Lactobacillus spp., levels to xylitol delivered via gummy bears at optimal exposures. Methods Children, first to fifth grade (n = 154), from two elementary schools in rural Washington State, USA, were randomized to xylitol 15.6 g/day (X16, n = 53) or 11.7 g/day (X12, n = 49), or maltitol 44.7 g/day (M45, n = 52). Gummy bear snacks were pre-packaged in unit-doses, labeled with ID numbers, and distributed three times/day during school hours. No snacks were sent home. Plaque was sampled at baseline and six weeks and cultured on modified Mitis Salivarius agar for S. mutans/sobrinus and Rogosa SL agar for Lactobacillus spp. enumeration. Results There were no differences in S. mutans/sobrinus and Lactobacillus spp. levels in plaque between the groups at baseline. At six weeks, log10 S. mutans/sobrinus levels showed significant reductions for all groups (p = 0.0001): X16 = 1.13 (SD = 1.65); X12 = 0.89 (SD = 1.11); M45 = 0.91 (SD = 1.46). Reductions were not statistically different between groups. Results for Lactobacillus spp. were mixed. Group X16 and M45 showed 0.31 (SD = 2.35), and 0.52 (SD = 2.41) log10 reductions, respectively, while X12 showed a 0.11 (SD = 2.26) log10 increase. These changes were not significant. Post-study discussions with school staff indicated that it is feasible to implement an in-classroom gummy bear snack program. Parents are accepting and children willing to consume gummy bear snacks daily. Conclusion Reductions in S. mutans/sobrinus levels were observed after six weeks of gummy bear snack consumption containing xylitol at 11.7 or 15.6 g/day or maltitol at 44.7 g/day divided in three exposures. Lactobacillus spp. levels were essentially unchanged in all groups. These results suggest that a xylitol gummy bear snack may be an alternative to xylitol chewing gum for dental caries prevention. Positive results with high dose maltitol limit the validity of xylitol findings. A larger clinical trial is needed to confirm the xylitol results. Trial registration [ISRCTN63160504]